Impact of Auger recombination parameterisations on predicting silicon wafer solar cell performance - Ma, Fa-Jun; Liu, Haohui; Liao, Baochen; Chen, Jia; Du, Zheren; Samudra, Ganesh S.; Aberle, Armin G.; Hoex, Bram; Peters, Ian Marius (Journal of Computational Electronics, 2014)
For high-efficiency silicon wafer solar cells, Auger recombination is becoming one of the most important efficiency limiting factors. For this purpose it is desirable to be able to use different Auger recombination parameterisations in advanced computer simulations. In this paper we present a method to implement arbitrary Auger parameterisations in the software package Sentaurus TCAD, enabling two- and three-dimensional simulation of solar cells using different Auger parameterisations. As examples, we implemented and investigated three different Auger parameterisations (proposed by Altermatt et al.; by Kerr and Cuevas, and by Richter et al.) from the literature. For verification, we simulate Auger lifetimes for different doping densities and injection levels in crystalline silicon. The simulated Auger lifetimes are found to agree well with analytical solutions (differences less than 0.001 %). We then employ the three different Auger parameterisations for fitting measured effective lifetime curves of both n -type and p -type float-zone silicon lifetime samples and show which models are applicable under which conditions. We further compare the difference between the three Auger parameterisations by simulating characteristics of a screen-printed aluminium local back surface field silicon wafer solar cell. The simulation results agree well with the characterisation results. We find that the choice of Auger parameterisation can lead to significant differences in the predicted solar cell behaviour under one-Sun illumination. We demonstrate that different Auger parameterisations may result in significant differences in the blue response, by simulating a heavily doped emitter of an aluminium local back surface field silicon wafer solar cell. © 2014 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Auger recombination; Carrier lifetime; Silicon solar cell; Simulation